Distance education unit "Mario Rizzini": a Salesian proposal - Pablo Farfán (Universidad Politécnica Salesiana, 2012)
The distance education unit Mario Rizzini is a Salesian educational program designed to help excluded sectors of society, mainly young people, whom due to their employment status, premature parenthood, exclusion from formal schools that do not consider special conditions, who failed to complete their education at a school age but feel now the need to graduate.This teaching style is based on social constructivism, wich allows the person to move forward from his/her own reality and knowledge, guided by the Salesian perspective with Don Bosco's charisma, using the preventive method as a means to achieve a fair society. The teaching strategies and instruments are developed from contemporary concepts of distance education, partucularly using information techonology, turned into virtual classrooms that guarantee continuous individual support for the learner. To summarize, we offer an educational alternative that according to our founder's charisma, attempts to include those in need but with high quality education.